A review of large-scale CO2 shipping and marine emissions management for carbon capture, utilisation and storage. (1st April 2021) - Al Baroudi, Hisham; Awoyomi, Adeola; Patchigolla, Kumar; Jonnalagadda, Kranthi; Anthony, E.J.
Highlights: Assessed CO2 shipping as a global decarbonisation strategy for future developments. Identified technical and safety challenges encountered during in CO2 shipping chain. Evaluated the environmental impact of shipping emissions in the transport chain. Summarised emission control technologies as a key enabler in the CO2 shipping chain. Abstract: Carbon Capture, Utilisation and Storage (CCUS) can reduce greenhouse gas emissions for a range of technologies which capture CO2 from a variety of sources and transport it to permanent storage locations such as depleted oil fields or saline aquifers or supply it for use. CO2 transport is the intermediate step in the CCUS chain and can use pipeline systems or sea carriers depending on the geographical location and the size of the emitter. In this paper, CO2 shipping is critically reviewed in order to explore its techno-economic feasibility in comparison to other transportation options. This review provides an overview of CO2 shipping for CCUS and scrutinises its potential role for global CO2 transport. It also provides insights into the technological advances in marine carrier CO2 transportation for CCUS, including preparation for shipping, and in addition investigates existing experience and discusses relevant transport properties and optimum conditions. Thus far, liquefied CO2 transportation by ship has been mainly used in the food and brewery industries for capacities varying between 800 m 3 and 1000 m 3 . However, CCUS requires much greater capacities and only limited work is available on the large-scale transportation needs for the marine environment. Despite most literature suggesting conditions near the triple-point, in-depth analysis shows optimal transport conditions to be case sensitive and related to project variables. Ship-based transport of CO2 is a better option to decarbonise dislocated emitters over long distances and for relatively smaller quantities in comparison to offshore pipeline, as pipelines require a continuous flow of compressed gas and have a high cost-dependency on distance. Finally, this work explores the potential environmental footprint of marine chains, with particular reference to the energy implications and emissions from ships and their management. A careful scrutiny of potential future developments highlights the fact, that despite some existing challenges, implementation of CO2 shipping is crucial to support CCUS both in the UK and worldwide.